A new NOTCH3 damaging variant in a thrombocytopenia family of Miao ethnic group. (22nd November 2019) - Zhao, Yingling; Li, Juheng
Abstract: Background: Pediatric inherited thrombocytopenia, also known as a deficiency of platelets in children, is caused by genetic factors and it is hard to obtain an effective treatment. Thus, it is necessary to identify the possible genetic variants that are responsible for thrombocytopenia. Methods: Whole exome sequencing was used to detect genetic variants in two members of a thrombocytopenia family of Miao ethnic group. Multiple in silico analyses were performed to evaluate the effects of the novel missense variants. Results: Finally, a novel variant (chr19: g.15170364G>A) in the NOTCH3 gene was found, as confirmed with Sanger sequencing, which could result in a R1694Q substitution in the protein. This variant was consistently suggested to be damaging by sift (Sorting Tolerant From Intolerant; http://sift.jcvi.org), polyphen (Polymorphism Phenotyping, version 2.0; http://genetics.bwh.harvard.edu/pph2) and mutationtaster (http://www.mutationtaster.org) software. By building the 3D model of the key region of NOTCH3 protein and performing the structure simulation, we found that (i) this variant affected the 3D structure model with a root‐mean‐square deviation = 0.46 between wild‐type and mutant type; (ii) this variant caused the protein to reduce the solvent accessible surface area by 421 Å 2 ; and (iii) compared to the wild‐type protein, the mutant protein had two less amino acids to maintain protein stability. Conclusions: A novel damaging variant in the NOTCH3 gene was identified in a thrombocytopenia family with respect to decreasing the stability of NOTCH3, which may help with the prognosis and therapy of inherited thrombocytopenia.